Tailoring morphology of hierarchical catalysts for tuning pore diffusion behaviour: a rational guideline exploiting bench-top pulsed-field gradient (PFG) nuclear magnetic resonance (NMR). Issue 7 (4th June 2020) - Forster, Luke; Lutecki, Michal; Fordsmand, Henrik; Yu, Le; D'Agostino, Carmine
Abstract : The aim of this work is to develop and quantify the tuning of transport properties in porous catalytic materials by tailoring their textural properties. Abstract : The aim of this work is to develop and quantify the tuning of transport properties in porous catalytic materials by tailoring their textural properties. In order to do this, alumina catalyst carriers were prepared from boehmite by varying preparation conditions to produce carriers with different pore sizes and macropore content. Pore size and macropore content decreased with boehmite mixing time and increased with calcination temperature due to alumina phase transformations occurring. Mass transport within the different materials was studied by pulsed-field gradient NMR diffusion techniques, with a low-field, bench-top NMR instrument, using n -octane as the probe molecule. The diffusion results revealed that mass transport occurs more readily in carriers with greater pore size and macropore content, by providing a comprehensive and quantitative description of this behaviour. In particular, up to a pore size of 17.0 nm diffusion increases very rapidly with pore size; at pore sizes greater than 17.0 nm and macropore content greater than 27% the major geometrical restrictions imposed by the pore structure on the probe molecule were removed and the diffusivity of guest molecules reaches a constant plateau, suggesting that a pore size greater than 17.0 nm and a macropore content greater than 27% do not lead to significant further improvements in mass transport properties. Diffusion studies using water, methanol and ethanol, as probe molecules with functional hydroxyl groups able to interact with the surface, showed that in samples with small pores and no amount of macropores, surface interactions of these guest molecules with the pore surface have a significant effect on determining the diffusive motion, in addition to the effect of the physical pore structure. For larger pores and larger macropore content, the surface chemistry of the pore walls has a much smaller impact on the diffusive motion inside the porous matrix. This work gives a comprehensive and quantitative overview on how to tailor carrier preparation procedures in order to tune mass transport, providing a rational guideline with important implications in design, preparation and applications of porous materials.